Review Pemagangan Luar Negeri Dalam Rangka Penempatan (Studi Mengenai Peraturan Menteri Tenaga Kerja dan Transmigrasi Nomor 08 Tahun 2008) - Andari Yurikosari (Jurnal Hukum PRIORIS, 2015)
The activity of an apprentice ships are in a particular agency or company. With the events of this internship, the students are expected to know about there all picture of the real world. This activity is also expected to the students to encourage their knowledge with the experience and skills to students before they actually plunge and compete in the world of work. Thus it will formearly work attitude, discipline, perseverance and honesty in students before they actually work. Apprentice ship program became one of the solutions to over come unemployment because it can increase human resources, broaden the knowledge and skills of job seekers work so easily absorbed in the world of work. Pattern trainee role as a bridge between the world of education of the needs of companies or jobs. The role of apprenticeship is very important, not merely for improving the quality of labor, but also can facilitate the companies in finding qualified workers and in accordance with the competencies they need. Carried out on the basis of apprenticeship agreement between participants with employers made in writing. Apprenticeship agreement shall contain the rightsand obligations of participant sand employers and apprentice shipperiod as stipulated in Act 13 of 2003 on employment. The form of the Government’s attention to the interns stipulated in Act 13 of 2003 on employment in particular ofArticles 21 to 30 and more specifically set forth in the Regulation of the Minister of Man power and Transmigration No. per 22/men/IX/2009 on the Implementation of Apprenticeship in the interior. With the regulations governing apprenticeship program is expected to legal protection againts violation of the rights-the right to apprentices and harmful things for both apprentices and corporate intern ships. Law No. 13 of 2003 on the Regulation of the Minister of Labour and Manpower and Transmigration No.PER.22/MEN/IX/2009 on the Implementation of Apprenticeship also regulate how the procedures and requirements about things-things related to apprenticeship, there for the legal protection of apprentices apprenticeship, especially in the country should going  well and fit because it has been stipulated in the laws or regulations of the minister. While some of the problems that occur based on a review of apprenticeship studies, the formulated some of the issues that will be studied as follows: how the implementation of foreign apprenticeship in Semarang, Central Java, Denpasar city of Bali Province, the city of Yogyakarta Special Region of Yogyakarta based on the laws and regulations regarding apprenticeship, how to identify requirements for the implementation and post a good apprenticeship in enterprises as well as in apprenticeship training institutions in accordance with the purpose of apprenticeship, what are the factors that lead to failure in over seas apprenticeship program associated with the expected output of the apprenticeship program and monitoring functions of the Department of Employment and apprenticeship how foreign policy recommendations are good, succesful, efficient for the company apprentices and interns in general. This type of research is chosen in this study is a normative legal research, because research aims to investigate the use of legislation apprenticeship at the Apprenticeship Training Center both government owned and private. In this case the authors examine and analyze legal materials in the form of regulations legislation.